A study of HPV self-sampling by female residents in communities of Zhengzhou, Henan Province, China: a cross-sectional observational study - Zhe Yang; Zhe Yang; Zhe Yang; Zhe Yang; Yue Lu; Yiping Zhang; Yunfeng Zhang; Jingyi Mu; Jingyi Mu; Jingyi Mu; Yicheng Li; Shihao Mei; et al. (Frontiers in Public Health, 2025)
ObjectiveEvaluate the feasibility of HPV self-sampling typing and quantitative detection as a cervical cancer screening scheme, and provide new methods to reduce the incidence of cervical cancer.MethodsThis was a cross-sectional observational study of 1,228 female residents in communities in Zhengzhou city, Henan Province, who participated in HPV self-sampling detection. All the samples were subjected to HPV typing and quantitative detection. HPV-positive individuals were recalled for further cervical liquid-based cytology and colposcopy.ResultsThe results of this study revealed that 33.71% of female residents lacked awareness of cervical cancer screening. Older age and low educational level are independent influencing factors for the lack of screening awareness. The overall positive rate of HPV was 18.89%. The three most common subtypes were types 16 (2.61%), 52 (2.44%), and 53 (2.28%). Results revealed that age at first sexual intercourse, sexual frequency, parity, having multiple sexual partners, cleaning behavior after sexual intercourse, and using condoms during sexual intercourse were factors related to HPV infection (P < 0.05). Logistic regression analysis revealed that age at first sexual intercourse ≤20 years, sexual frequency >2 times/week, parity >1 time, and having multiple sexual partners were risk factors for HPV infection (OR > 1, P < 0.05). Frequent cleaning after sexual intercourse and frequent use of condoms during sexual intercourse were protective factors against HPV infection (OR < 1, P < 0.05).ConclusionHPV self-sampling detection had a good experience and a high degree of acceptance, which can be promoted and applied in cervical cancer screening in Henan province.